2000
DOI: 10.1023/a:1011185806974
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A hydrocarbon degrader isolated from a chronically oil-polluted marine site was identified as Rhodococcus sp. on the basis of morphology, fatty acid methyl ester pattern, cell wall analysis, biochemical tests and G + C content of DNA. It degraded up to 50% of the aliphatic fraction of Assam crude oil, in seawater supplemented with 35 mM nitrogen as urea and 0.1 mM phosphorus as dipotassium hydrogen orthophosphate, after 72 h at 30 degrees C and 150 revolutions per minute. The relative percentage of intracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(8 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Interestingly, the aromatic benzene compounds and its derivatives were effectively degraded in 120 h and elucidated by the accumulation of benzoic acid, 4-ethoxy at Rt (40.324) and 1, 2-benzenedicarboxylic acid at Rt (55.622), respectively. The accumulation of carboxylic acids corroborated with the research findings of Sharma and Pant (2000) 14 . At 10 MPa culture conditions, the major end product benzyl alcohol ( Rt 17.902) was observed within 72 h of incubation (Table 2).…”
Section: Resultssupporting
confidence: 87%
“…Interestingly, the aromatic benzene compounds and its derivatives were effectively degraded in 120 h and elucidated by the accumulation of benzoic acid, 4-ethoxy at Rt (40.324) and 1, 2-benzenedicarboxylic acid at Rt (55.622), respectively. The accumulation of carboxylic acids corroborated with the research findings of Sharma and Pant (2000) 14 . At 10 MPa culture conditions, the major end product benzyl alcohol ( Rt 17.902) was observed within 72 h of incubation (Table 2).…”
Section: Resultssupporting
confidence: 87%
“…They reported that the surfactin started to precipitate out of the production medium at pH 5 and was dissolved completely when the pH returned to 6.1. As a result, physical characterization revealed that the surfactin has excellent surface and emulsifying activities and it showed high stabilities over a wide pH range (5)(6)(7)(8)(9)(10). These properties make the surfactin biosurfactant potential candidate to be used in the bioremediation of contaminated sites and in the petroleum industry (MEOR) where drastic conditions commonly prevail.…”
Section: Phmentioning
confidence: 99%
“…Biosurfactants are widely used in different industries, such as cosmetics, special chemicals, food, pharmaceutics, agriculture, cleaners and microbial enhanced oil recovery (MEOR) [10][11][12][13]. The last mentioned application has attracted more attention because only 30% of oil present in reservoir can generally be recovered using primary and secondary recovery techniques [1].…”
Section: Introductionmentioning
confidence: 99%
“…In the genome of strain 7B, there are gene clusters of heterobactin and erythrochelin production, as well as individual elements related to the gene cluster of atratumycin production. Atratumycin is a cyclodepsipeptide with activity against Mycobacteria tuberculosis isolated from deep-sea derived Streptomyces atratus [53] . In turn, erythrochelin is a hydroxamate-type siderophore, the production of which is characteristic of Saccharopolyspora erythraea [54] .…”
Section: Resultsmentioning
confidence: 99%